Organizational culture for development business of Bucaramanga - Pineda Castillo, Hernando (Rastros Rostros, 2011)
The research project “Production of teaching materials to apply a productivity and competitiveness system in business” was done in the Universidad Cooperativa de Colombia, Bucaramanga (2008-2010) with the purpose of collaborates in the context of the region. The municipality of Bucaramanga summary presents certain characteristics in the medium-sized and micro and small companies identified as SMMEs which form part of the sectors more important from the local industry, being necessary and final to establish a planning and management for the development of investment strategies, production, structural changes in the technology, training and networking, to make them much more competitive and productive in order to comprehensively strengthen regional inputproduction chains.
Keywords: Demand; Globalization; Supply; Organization; Supplier